Intestinal absorption and cell transforming potential of PhIP-M1, a bacterial metabolite of the heterocyclic aromatic amine 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP). Issue 2 (16th April 2015) - Nicken, Petra; Willenberg, Ina; Keutz, Anne von; Elsner, Leonie von; Hamscher, Gerd; Vanhaecke, Lynn; Schröder, Bernd; Breves, Gerhard; Schebb, Nils Helge; Steinberg, Pablo
Highlights The transport of PhIP-M1, a metabolite of the colon carcinogen PhIP produced by gut bacteria, in eight different intestinal segments from male Fischer 344 rats was examined in Ussing chambers. A very recently developed HPLC method to quantify the concentration of PhIP-M1 in biological fluids as well as in intestinal tissue was applied. At the most, 10–20% of the PhIP-M1 amount added to the mucosal compartment of the Ussing chambers per segment were absorbed within 90 min. PhIP-M1 in a concentration of up to 100 μM did not induce the malignant transformation of BALB/c 3T3 cells. Even if one would assume that 100% of the daily amount of PhIP ingested by a human being is converted into PhIP-M1 in the colon, this concentration most probably would not lead to carcinogenicity in the colorectal mucosa.